Patterns of attendance in the maternity ward of Kuruman District Hospital 2006 - 2009 - Dijong, Keobiditse Dawn (My University, 2012)
Maternal health services have been receiving increasing attention internationally. The high rates of maternal and infant mortality throughout the world place a demand on health systems to prioritize maternal and child health care services. The constitution of South Africa recognizes reproductive health as a fundamental right (Republic of South Africa, 1995). However, the inability of South Africa to meet the Millennium Development Goals targets for maternal and child health increases the need for more studies to identify the reasons for a consistently high maternal mortality rate. The South African health system is based on district health system model which facilitates the delivery of primary health care and the appropriate referrals and admissions of patients. District hospitals, public and private community health centers and public primary health care clinics provide the first level of care to patients. Normal deliveries should take place at this level. Referrals are made to secondary and tertiary level of care. The maternity ward at Kuruman Hospital in the Northern Cape province of South Africa is overcrowded. There are concerns around the quality of care and over 80% of deliveries are normal, suggesting that they could take place at the primary health care clinics and community health centres in the district.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilmet of the requirement fo rthe Degree of Masters of Public Health. April 2012
Keywords: Maternal Health Services--Northern Cape--South Africa